2023
DOI: 10.3390/biology12111453
|View full text |Cite
|
Sign up to set email alerts
|

Polyherbal and Multimodal Treatments: Kaempferol- and Quercetin-Rich Herbs Alleviate Symptoms of Alzheimer’s Disease

Claire Alexander,
Ali Parsaee,
Maryam Vasefi

Abstract: Alzheimer’s Disease (AD) is a progressive neurodegenerative disorder impairing cognition and memory in the elderly. This disorder has a complex etiology, including senile plaque and neurofibrillary tangle formation, neuroinflammation, oxidative stress, and damaged neuroplasticity. Current treatment options are limited, so alternative treatments such as herbal medicine could suppress symptoms while slowing cognitive decline. We followed PRISMA guidelines to identify potential herbal treatments, their associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 367 publications
0
3
0
Order By: Relevance
“…Medicinal plants and herbal remedies are also becoming relevant as complementary interventions, providing a valuable source for drug development for neurodegenerative diseases [27][28][29]. This global use is driven by a strong interest in younger and older generations to improve cognitive performance and achieve healthy aging [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Medicinal plants and herbal remedies are also becoming relevant as complementary interventions, providing a valuable source for drug development for neurodegenerative diseases [27][28][29]. This global use is driven by a strong interest in younger and older generations to improve cognitive performance and achieve healthy aging [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…At present, many studies on the pharmacological effects of Quercetin are not mature, the drugs with Quercetin as the main component are relatively few, and can not be widely used in clinical treatment (Paula et al, 2019). Quercetin and its active components can inhibit Aβ toxicity, Tau protein hyperphosphorylation and neuronal apoptosis through a variety of mechanisms, thus preventing and treating AD (Alexander et al, 2023). Recent studies have found that Quercetin can enhance autophagy and accelerate the clearance of Tau protein, thus protecting the nervous system (Vaiserman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin (Qu), a flavonoid commonly present in traditional Chinese herbs as well as everyday fruits and vegetables like apples, bananas, onions, and leeks, exhibits promising potential for various applications due to its wide availability in various foods . The antioxidant, anti-inflammatory, and neuroprotective properties of Qu have prompted extensive research into its therapeutic efficacy in the treatment of neurodegenerative diseases .…”
Section: Introductionmentioning
confidence: 99%